Insect herbivory increases from forest to alpine tundra in Arctic mountains - Zvereva Elena L.; Zverev Vitali; Kozlov Mikhail V. (WILEY, 2022)
Current theory holds that the intensity of biotic interactions decreases with increases in latitude and elevation; however, empirical data demonstrate great variation in the direction, strength, and shape of elevational changes in herbivory. The latitudinal position of mountains may be one important source of this variation, but the acute shortage of data from polar mountains hampers exploration of latitude effects on elevational changes in herbivory. Here, we reduce this knowledge gap by exploring six elevation gradients located in three Arctic mountain ranges to test the prediction that a decrease in herbivory occurs with increasing elevation from forest to alpine tundra. Across the 10 most abundant evergreen and deciduous woody plant species, relative losses of foliage to insect herbivores were 2.2-fold greater at the highest elevations (alpine tundra) than in mid-elevation birch woodlands or low-elevation coniferous forests. Plant quality for herbivores (quantified by specific leaf area) significantly decreased with elevation across all studied species, indicating that bottom-up factors were unlikely to shape the observed pattern in herbivory. An experiment with open-top chambers established at different elevations showed that even a slight increase in ambient temperature enhances herbivory in Arctic mountains. Therefore, we suggest that the discovered increase in herbivory with elevation is explained by higher temperatures at the soil surface in open habitats above the tree line compared with forests at lower elevations. This explanation is supported by the significant difference in elevational changes in herbivory between low and tall plants: herbivory on low shrubs increased fourfold from forest to alpine sites, while herbivory on trees and tall shrubs did not change with elevation. We suggest that an increase in herbivory with an increase in elevation is typical for high-latitude mountains, where inverse temperature gradients, especially at the soil surface, are common. Verification of this hypothesis requires further studies of elevational patterns in herbivory at high latitudes.